PENYELESAIAN TA’ARUDH AL-ADILLAH DALAM PENGHARAMAN RIBA FADHL - Abiyyu Mahir Ammar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Riba/usury is agreed to be forbidden in Islam. There are two general opinions about the criteria for usury that is forbidden, especially usury on debt. First, that all additional forms in debt and credit transactions are in the form of usury, and the second opinion argues that there must be an element of oppression, multiplication, etc. in order to be called usury. This is due to the lack of clarity on the criteria for usury in the Qur'an. So in this article the author tries to strengthen the opinion that all additions, a little or a lot, are usury. This is based on the qiyas aula, most of scholars agree that riba fadl is forbidden, even though the excess of one of the items is small. Meanwhile, if observed, riba fadl which is an unequal weight or size of one of usury goods in buying and selling or bartering whose purpose is to make a profit is not allowed. Thus, it is preferable to add additional prohibitions on debt usury, which aims to help someone. However, the argument that prohibits riba fadl is only found in the hadith, even more there are hadiths that at first glance contradict each other regarding the prohibition of usury fadl or buying and selling. So, the contradictife arguments need to be resolved so that the prohibition of riba fadl can be used as a comparison against the prohibition of usury nasi'ah/debts.